STUDI MUTU BUAH KELAPA SAWIT (Elaeis guineensis Jacq.) PADA BERBAGAI UMUR TANAMAN DI LAHAN GAMBUT - Prayogi, Akhlul; Khoiri, M Amrul; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to determine the relationship of the best quality oil palm at the different age of plants in peatlands. The method used in this research is the survey method using diagonal sampling 5% of the land area in order to obtain 27 plants of all plants ages (6, 7 and 9 years old). The data analyzed were fresh weight, dry weight, volume of fruit, thick mesocarp, water capacity, oil return and free fatty acid of oil palm. Data were analyzed using the t test and correlation at the 5% level. The results showed the age of the plant affects the weight of fresh fruit, fruit, dry weight and the volume of oil palm fruits, but did not affect the mesocarp thickness, the water capacity of fruit, oil content and free fatty acid of oil palm fruit. Based on the quality standards of oil palm fruits PTPN V (2007) in this study, plant with age 6, 7 and 9 years old have bad fruit, water capacity, good oil yield fruit and free fatty acid with medium quality of fruit. Keywords: age, oil palm, peatlands, quality